Physicochemical properties and diversity of microbial communities in soil associated with fusarium wilt disease of banana in Selangor, Malaysia - Jamil, Fatin Nadiah (2021)
Fusarium wilt (FW) is a soilborne disease caused by the fungal pathogen, Fusarium oxysporum f. sp. cubense (Foc) which jeopardizes the banana industry worldwide including Malaysia. Studies have shown that soil microbiome and its physicochemical properties are associated with the outbreak of FW. Rhizosphere and bulk soil microbiome help in the plant growth and also the defense system. Identification of biomarker identification with strong positive correlation with soil physicochemical properties from the healthy soils of banana is critical for construction of disease suppressive soil. Aside from that, a combination biomarkers of healthy soil with ability to promote plant growth, could be used as a bio-fertilizer and biocontrol agent to control the FW diseased caused by TR4. However, little is known about the diversities of the fungal and bacterial microbiome associated with diseased or healthy sites within the banana field in Malaysia or the difference in soil properties which may lead to poor disease management. This study applied 16S rRNA amplicon and internal transcribed spacer (ITS) sequencing analysis to investigate microbial diversity and community structure in Berangan banana farm in Sabak Bernam, Selangor. Both fungal and bacterial richness and diversity were significantly higher in the FW-infected soils compared to healthy soils. Similar to previously reported studies, the microbial community of healthy and FW-infected soil was more diverse in the rhizosphere than bulk soil. The potential bacterial biomarkers associated with the healthy soil were Burkholderia and Streptomyces spp., while Xanthomonadaceae, Sphingomonas, Azospira oryzae, Pseudomonas and Acinetobacter tandoii were highly abundant in FW-infected soil. For fungal biomarker taxa, Penicillium sp. was identified as the dominant fungus in healthy soil, while Trichothecium ovalisporum, Nectriaceae and Sarocladium strictum were dominant in FW-infected soil. In physicochemical properties, only magnesium (Mg) and cation exchange capacity (CEC) were found highly significant (t-test, p < 0.05) in the healthy soils compared to the infected soils. For 16S, a Canonical correspondence analysis (CCA) showed a positive correlation of Mg with Bradyrhizobium sp. and Acidobacteriaceae in rhizosphere healthy (RH) soil for maintaining soil health. Meanwhile in ITS, a positive correlation was found between Penicillium sp. with Mg, suggesting the production of Mg was associated with metabolites secreted by Penicillium sp., which could control the disease caused by microbes. Overall, this study reported differences in the key taxa of rhizosphere soil microbial communities and soil physicochemical properties between healthy and FW-infected plants, suggesting their potential role as indicators for banana health. This specific information is applicable for constructing a healthy microbial community structure as the sustainable control strategy against TR4. Thus, in order to apply the biofertilizer or biocontrol agent, further study is needed to study the potential of network interaction between the microbial diversities and their functional behaviors and pathways in rhizosphere and bulk soil for long term disease control.